Non-epileptic myoclonus status can be due to both SARS-CoV-2 infection and SARS-CoV-2 vaccination. (March 2023) - Finsterer, Josef
Keywords: SARS-CoV-2; Vaccination; Myoclonic status; EEG; COVID-19; Seizure